Comparative estimation of the effectiveness of the Khorana, Vienna CATS, and TiC-Onco scores and the vWF/ADAMTS13 ratio in identifying a high risk of thrombotic complications in patients with malignant neoplasms - A. V. Vorobеv; A. G. Solopova; V. O. Bitsadze; M. M. Baeva; M. E. Sosnyagova; V. N. Galkin; D. O. Utkin; A. D. Makatsariya (Фармакоэкономика)
Objective: To compare the diagnostic accuracy of the Khorana, Vienna CATS, and TiC-Onco scores in assessing the risk of venous thromboembolism (VTE) in patients with malignant neoplasms of the female reproductive system and mammary gland and to evaluate the prognostic role of the vWF/ADAMTS13 ratio in identifying groups with a high risk of thrombosis.Material and methods. The study included 108 female patients with confirmed malignant neoplasms of the reproductive system and mammary gland (stages I–III), who were assessed for VTE risk using the Khorana, Vienna CATS, and TiC-Onco scores. In all the patients, the levels of von Willebrand factor (vWF) and a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13 (ADAMTS13) were measured followed by calculation of their ratio. According to the final points obtained by each score, the patients were classified into the subgroups of a high, medium, and low risk of thrombosis. Concurrently, the presence of earlier thrombosis was analyzed. The sensitivity and specificity of the identified threshold values were assessed.Results. According to the Khorana score, 33 patients scored ≥3 points, of which 24 had thrombotic complications. The Vienna CATS score, due to the inclusion of the D-dimer level, demonstrated a slightly higher detection rate of true thrombogenic cases (54.2% instead of 50%); however, the performance of this score in differentiation between false positive and false negative cases was not always high. The TiC-Onco risk score, which includes genetic markers of thrombophilia, increased the proportion of high-risk detection in VTE patients (up to 64.6%), although increasing the proportion of false positive cases, i.e. patients without thrombosis who formally got high scores. The vWF/ADAMTS13 threshold ≥1.6 showed the highest specificity (only 8.3% of false positive cases) and detected 70.8% of truly thrombogenic episodes, which indicates a high sensitivity of this marker.Conclusion. The Khorana, Vienna CATS, and TiC-Onco scores demonstrate moderate accuracy in predicting thrombosis in cancer patients, partly due to their inability to consider the individual characteristics of endothelial dysfunction and/or overestimation of the impact of “silent” genetic mutations. Inclusion of the vWF/ADAMTS13 ratio in the observation algorithm, particularly at a threshold value of ≥1.6, provides for a clearer VTE risk stratification, thus showing promise as a priority criterion when deciding on antithrombotic therapy in patients with malignant neoplasms of the female reproductive system and mammary gland.